Theoretical numerical analysis an introduction to advanced techniques - Linz, Peter (Dover Publications, 2019)
Concise text focuses on fundamentals of functional analysis and approximation theory, the major results of theoretical numerical analysis, and specific topics that illustrate the power and usefulness of theoretical analysis. 1979 edition